The Effect of Digital Literacy on Social Comparison-Related Insecurity on Instagram among University Students - Emma Triadelina Hutabarat (Journal of Smart Education and Emerging Technology, 2025)
Background/Context: The widespread use of Instagram among university students has intensified exposure to curated online content, increasing the likelihood of upward social comparison. Such comparisons may contribute to feelings of insecurity and negatively affect students’ psychological well-being. Although digital literacy is often considered a protective factor in navigating social media content, its direct influence on insecurity remains unclear.Objective/Purpose: This study aims to examine the effect of digital literacy on students’ insecurity resulting from social comparison on Instagram.Method: The research employed a quantitative explanatory design. Data were collected from active Instagram-using university students through an online Likert-scale questionnaire. Data analysis included normality testing using the Kolmogorov–Smirnov and Shapiro–Wilk tests, followed by simple linear regression analysis.Results: Normality testing indicated that the insecurity variable was not normally distributed (Kolmogorov–Smirnov, p = 0.003; Shapiro–Wilk, p = 0.005). Regression analysis revealed a very weak and non-significant relationship between digital literacy and insecurity (R = 0.192; R² = 0.037; B = 0.361; p = 0.292). These findings suggest that digital literacy does not significantly predict students’ insecurity related to social comparison on Instagram.Conclusion: The study concludes that digital literacy alone is insufficient to significantly reduce insecurity arising from social comparison on Instagram. Other psychological or contextual factors may play a more substantial role. However, digital literacy remains essential for fostering critical evaluation of social media content and supporting healthier emotional regulation in digital environments